On the Question of the Ground of Fredric Jameson’s Postmodern Dialectic - O'Donnell, Liam (Cosmos and History: The Journal of Natural and Social Philosophy, 2023)
This paper examines Fredric Jameson’s attempt to formulate a postmodern dialectic in his text, Valences of the Dialectic. Such a project is necessary, according to Jameson, because dialectical thought is immanent to the movement of history, and the latest epoch of history that we find ourselves caught within is that of postmodernity. Epochality and history are totalising concepts, and so we can see immediately that there is a tension between Jameson’s historicist method (and presuppositions), and the prioritising of difference and non-identity that characterises postmodernism. What Jameson aims to do, therefore, is to reveal how the dialectical concepts of totality and contradiction can be thought in such a way that they are compatible with the postmodern prioritising of difference and non-identity. He aims to do this by arguing that history itself, understood in its most profound sense rather than its everyday sense, is an unrepresentable ground existing behind, and beyond, the manifold beings of our world as their condition of possibility. Jameson claims that our access to this deeper reality of history can only emerge indirectly through our awareness of the antinomies of thought and experience.